Spring understory herbs flower later in intensively managed forests. Issue 5 (26th May 2021) - Willems, Franziska M.; Scheepens, J. F.; Ammer, Christian; Block, Svenja; Bucharova, Anna; Schall, Peter; Sehrt, Melissa; Bossdorf, Oliver
Abstract: Many organisms respond to anthropogenic environmental change through shifts in their phenology. In plants, flowering is largely driven by temperature, and therefore affected by climate change. However, on smaller scales climatic conditions are also influenced by other factors, including habitat structure. A group of plants with a particularly distinct phenology are the understory herbs in temperate European forests. In these forests, management alters tree species composition (often replacing deciduous with coniferous species) and homogenizes stand structure, and as a consequence changes light conditions and microclimate. Forest management should thus also affect the phenology of understory herbs. To test this, we recorded the flowering phenology of 16 early‐flowering herbs on 100 forest plots varying in management intensity, from near‐natural to intensely managed forests, in central and southern Germany. We found that in forest stands with a high management intensity, such as Norway spruce plantations, the plants flowered on average about 2 weeks later than in unmanaged forests. This was largely because management also affected microclimate (e.g., spring temperatures of 5.9°C in managed coniferous, 6.7 in managed deciduous, and 7.0°C in unmanaged deciduous plots), which in turn affected phenology, with plants flowering later on colder and moister forest stands (+4.5 d per −1°C and 2.7 d per 10% humidity increase). Among forest characteristics, the percentage of conifers had the greatest influence on microclimate, but also the age, overall crown projection area, structural complexity and spatial distribution of the forest stands. Our study indicates that forest management alters plant phenology, with potential far‐reaching consequences for the ecology and evolution of understorey communities. More generally, our study demonstrates that besides climate change other drivers of environmental change, too, can influence the phenology of organisms.